The Hospital Characteristics (Public and Private) Utilization by Caesarean Section Delivery in Thailand - Arifah Devi Fitriani; Razia Begum Suroyo; Teguh Suharto; Manisha Manisha; Farachdiba Farachdiba; Maretalinia Maretalinia (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Cesarean delivery (C-section) rates continue to rise worldwide, with Thailand showing a significant spike in the past two decades, surpassing WHO recommended rates. Hospital characteristics, such as ownership, financial incentives, and medical staffing patterns, can influence cesarean delivery rates. Private hospitals may be more susceptible to non-medical motivations, while public hospitals often face high patient volumes and resource constraints. This study aimed to investigate the use of cesarean delivery in relation to hospital characteristics, with a comparative focus between public and private hospitals in Thailand. This study used a cross-sectional quantitative approach with secondary data from the Thailand Multi Indicator Survey (MICS) 2022. The study sample consisted of 1,046 women who delivered by cesarean section and 1,720 women who did not, with the dependent variable being hospital utilization by caesarean section delivery. Data analysis was performed using univariate, bivariate (Chi-square test), and multivariate (binary logistic regression) tests to analyze the effect of independent variables on the choice of hospital type. The study findings were that in women undergoing cesarean section, wealth and region of residence were significantly associated with private hospital utilization, with women from the fourth wealth quintile (OR = 14.61; 95% CI: 1.88–113.85) and the richest (OR = 23.67; 95% CI: 3.03–185.09) more likely to use private hospitals than the poorest, while those living outside Bangkok were less likely. In women without cesarean section, living in rural areas (OR = 0.36; 95% CI: 0.16–0.81) and outside Bangkok also significantly decreased the odds of private hospital utilization.